VD_FINDINFO Jug / 2024 / 62 vom 6. Oktober 2023 - VD Tribunal cantonal (2023)
LIBÉRATION CONDITIONNELLE, RÉVOCATIONEN GÉNÉRAL, CONCOURS D'INFRACTIONS | 49 CP, 89 CP, 95 al. 1 let. b LCR, 115 al. 1 let. b LEI